Numerical Analysis to Assess the Vertical Drainage Within Flexible Pavement. - Al-Adili, Aqeel; H. Abdul-Amir, Rasha; Hassan Chfat, Osamah (International Journal of Engineering and Technology, 2018)
In this research the work methodology include the software program SEEP/W routine of the GEOSLOPE 2012; which was used to simulate and analyze the vertical drainage of the pavement cross section using steady-state and transient analysis. A laboratory model consisting of typical structure layers of flexible pavement was considered in this research with a 2% slope with the influence of three different rain intensities (30mm/min, 60mm/min and 90mm/min); in which each one has a duration differs from the other. The results indicated that the value of the pore-water pressure in the surface layer resulting from 90 mm/min rainfall intensity is 83.65% greater than the pressure generated by the 60mm/min intensity of rain and 91.076% greater than the pressure produced from 30mm/min intensity. The average of accumulation water produced by the 30mm/min rainfall intensity in the pavement structure is 44.73 % greater than the average of accumulation of water from the 60mm/min intensity and 77.85% higher than the 90mm/min intensity of rain. The water flux through the pavement cross section during the rainy period of 30 mm/min was 8.42% higher than the water flux of 60 mm/min and 49.82% of the water flux of 90 mm/min intensity of rain.Â Â